(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article is devoted to the analysis of indicators of the banking sector in Russia. Research objectives: a consideration of the indicators of the banking system in dynamics, an identification of problem areas, this sector development forecast. The importance of conducting a rational monetary policy for the stabilization of the banking sector and its further development is emphasized. The formulated conclusions make an additional contribution to a comprehensive study of the problem of the banking sector functioning.